INFLUENCE OF FORMAL STRUCTURES ON SUSTAINABLE PERFORMANCE CONTRACTING OF EMPLOYEES IN CHARTERED PUBLIC UNIVERSITIES IN KENYA - Amwayi, Joshua Enane; Iravo, Prof. Mike Amuhaya; Odhiambo, Prof. Romanus; Lutsili, Dr. Victor Ladan (Journal of Human Resource and Leadership, 2018)
Purpose: The study at investigating the influence of formal structures on sustainable performance contracting of employees in chartered public universities in Kenya Methods: The study adopted a descriptive research design. This study adopted a positivist research philosophy. The population of the study comprised of all the staff members in public chartered universities in Kenya. For this study, target population was 27,054. This figure comprised of various staff at the universities who included; the Academic, Administrative and Technical staff. Various strata were identified from the areas of academic specialization of schools or faculties. The sample size was 384 respondents. Primary data was collected by use of one main structured questionnaire that captured the various variables of the study. Both descriptive and inferential statistics were used. Results: Formal structures as an element of institutional framework influenced sustainable performance contracting of employees in chartered public universities in Kenya through providing the policy framework as well as rules and regulations for the development and implementation of the performance contracts. Unique contribution to theory, practice and policy: The study recommends that the management of the chartered public universities in Kenya should conduct regular review of the institutions' formal structures in order to ensure that they remain up to date; are reflective of the changes happening within the institutions and also enhance the employees' performance. Keywords: Formal structures, sustainable performance contracting, employees, chartered public universities